Autoimmune findings in patients with silicosis in Spain - Coral González Fernández; Jose Antonio Ros Lucas; Maria Molina Molina; Juan Rigual Bobillo; Rogelio Alejandro García Montenegro; Raquel Fernández González; Ana Jaureguiza Oriol; Jose Abal Arca (BioExcel Publishing Ltd, 2024)
Background: Occupational exposure to silica is related to autoimmune diseases and features of autoimmunity, mainly autoantibodies. The study objectives were to estimate the prevalence of silicosis with associated autoimmune findings or diagnosed autoimmune diseases in Spain, and to assess the clinical and functional characteristics of affected patients. Methods: This is a multicentre prospective study in patients diagnosed with silicosis. Autoantibodies analysed were antinuclear antibodies, isotypes IgA, IgM and IgG, rheumatoid factor, anticyclic citrullinated peptide, anti-Scl70, anti-Ro, and anti-LA. Pulmonary function tests were performed. Results: Autoimmunity was assessed in 105 patients. Autoimmune findings were recorded in 29 (27%) patients, including antinuclear antibodies (n=21), anti-Ro (n=7), rheumatoid factor (n=5) and anti-Scl70 (n=3). Autoimmune disease was diagnosed in 16 (15%) patients, mainly rheumatoid arthritis (n=7) and systemic lupus erythematosus (n=4). Patients with silicosis and autoimmune findings had a lower mean time of exposure to silica and showed a trend toward lower values in pulmonary function tests. Conclusions: Autoimmune findings and diagnosis of autoimmune diseases were frequent in patients with silicosis in Spain.